The Role of Ethanol in the Brazilian Economy: Three Decades of Progress - Joaquim Guilhoto; Cinthia Costa; Marcelo Cunha; Kathleen Araujo (European Regional Science Association (ERSA), 2011)
Sustainable energy strategies require decision-makers in government, industry, academia and civil society alike to make choices among tradeoffs. Within the transport sector alone, ethanol has been shown to be the dominant solution among viable, low carbon options to date, yet questions remain over the economic and ecological impacts of this industry. In Brazil - the largest producer of sugarcane-based ethanol and a country with over three decades of ethanol development - we find a strong basis for evaluating the ethanol industry's role in a national economy. In the mid 1970's, Brazilian ethanol production received an important boost with the launch of the "Proálcool" program. The ethanol industry has subsequently evidenced flux until its consolidation in the period following 2000. Over the course of three decades, economic, institutional, technological and environmental determinants have factored in the success of Brazilian ethanol diffusion. In economic terms, price tradeoffs for ethanol vs. sugar and ethanol vs. gasoline played a role in scale-up of the biofuel together with balance of payment considerations. From an institutional standpoint, support for the Proálcool program, deregulation of the sugar-cane sector in the 1990's and fuel pump adaptations also factored. With respect to technology, the development of flex fuel cars, greater use of mechanized harvesting, and launch of domestic, co-generated, electrical power were key drivers. Finally, in environmental terms, challenges associated with pollution and public health in major cities as well as questions related to climate change gained visibility. In this paper, we analyze a set of input-output tables for the Brazilian economy from 1975 to 2008, taking the above factors into consideration. Deriving a series of indicators, such as multipliers and linkages, we study the evolution of the ethanol sector's role in the Brazilian economy and its relation to the productive structure of the country.
Keywords: 330